Neuropathic Pain Up-Regulates Hypothalamo-Neurohypophysial and Hypothalamo-Spinal Oxytocinergic Pathways in Oxytocin-Monomeric Red Fluorescent Protein 1 Transgenic Rat. (15th May 2019) - Nishimura, Haruki; Kawasaki, Makoto; Suzuki, Hitoshi; Matsuura, Takanori; Motojima, Yasuhito; Ohnishi, Hideo; Yamanaka, Yoshiaki; Yoshimura, Mitsuhiro; Maruyama, Takashi; Saito, Reiko; Ueno, Hiromichi; Sonoda, Satomi; et al.
Abstract: Despite the high incidence of neuropathic pain, its mechanism remains unclear. Oxytocin (OXT) is an established endogenous polypeptide produced in the supraoptic nucleus (SON) and paraventricular nucleus (PVN) of the hypothalamus. OXT, which is synthesized by OXT neurons in the SON and the magnocellular part of the PVN (mPVN), is delivered into the posterior pituitary (PP), then released into the systemic blood circulation. Meanwhile, OXT-containing neurosecretory cells in the parvocellular part of the PVN (pPVN) are directly projected to the spinal cord and are associated with sensory modulation. In this study, the OXT system in the hypothalamo-neurohypophysial and hypothalamo-spinal pathway was surveyed using a rat neuropathic pain model induced by partial sciatic nerve ligation (PSL). In the present study, we used transgenic rats expressing an OXT-monomeric red fluorescent protein 1 (mRFP1) fusion gene. In a neuropathic pain model, mechanical allodynia was observed, and glial cell activation was also confirmed via immunohistochemistry. In this neuropathic pain model, a significant increase in the OXT-mRFP1 expression was observed in the PP, the SON, mPVN, and pPVN. Furthermore, OXT-mRFP1 granules with positive fluorescent reaction were remarkably increased in laminae I and II of the ipsilateral dorsal horn. Although the plasma concentrations of OXT did not significantly change, a significant increase of the mRNA levels of OXT and mRFP1 in the SON, mPVN, and pPVN were observed. These results suggest that neuropathic pain induced by PSL upregulates hypothalamic OXT synthesis and transportation to the OXTergic axon terminals in the PP and spinal cord. Highlights: We examined OXT system in a neuropathic pain model induced by PSL. We used transgenic rats express an OXT and mRFP1 fusion gene for all experiments. The expression of OXT-mRFP1 was increased in the neuropathic pain model. Gene expression of OXT and RFP1 mRNA was increased in the neuropathic pain model. Neuropathic pain upregulates OXT synthesis and supply to the spinal cord.